2020
DOI: 10.1242/jcs.236786
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Morgana is an Hsp90-interacting protein with a direct role in microtubule polymerisation

Abstract: Morgana (Mora, also known as CHORD in flies) and its mammalian homologue, called CHORDC1 or CHP1, is a highly conserved cysteine and histidine-rich domain (CHORD)-containing protein that has been proposed to function as an Hsp90 co-chaperone. Morgana deregulation promotes carcinogenesis in both mice and humans while, in Drosophila, loss of mora causes lethality and a complex mitotic phenotype that is rescued by a human morgana transgene. Here, we show that Drosophila Mora localises to mitotic spindles and co-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…CHORDC1, as other HSP90 co-chaperones, suppresses the aggregation of denatured proteins. HSP90 and its co-chaperones mediate protein conformation shifts during the cell cycle [17]. It has been shown that reduction of CHORDC1 leads to defective chromosome condensation and spindle formation, as well as tumorigenesis, as a result of altered HSP90 activity [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHORDC1, as other HSP90 co-chaperones, suppresses the aggregation of denatured proteins. HSP90 and its co-chaperones mediate protein conformation shifts during the cell cycle [17]. It has been shown that reduction of CHORDC1 leads to defective chromosome condensation and spindle formation, as well as tumorigenesis, as a result of altered HSP90 activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…HSP90 and its co-chaperones mediate protein conformation shifts during the cell cycle [17]. It has been shown that reduction of CHORDC1 leads to defective chromosome condensation and spindle formation, as well as tumorigenesis, as a result of altered HSP90 activity [17]. RTN4 belongs to the family of reticulon encoding genes which are associated with the endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the cells, Morgana regulates signal transduction by binding and inhibiting Rho kinases I and II ( Ferretti et al, 2010 ; Fusella et al, 2014 ) and promotes NF-kB activation ( Fusella et al, 2017 ). It is also involved in microtubule polymerization ( Palumbo et al, 2020 ), EGF receptor trafficking ( Haag et al, 2020 ), and extracellular vesicle secretion ( Urabe et al, 2020 ). We recently found that Morgana is secreted by several cancer cells through an unconventional pathway and it associates with HSP90 in the extracellular milieu.…”
Section: Ehsp90 Complexes Activate Cancer Cell Surface Receptorsmentioning
confidence: 99%
“…Morgana is a ubiquitous chaperone protein, essential for Drosophila and mouse development [1][2][3] . Morgana binds to the Heat Shock Protein 90 (HSP90) 1,2,[4][5][6][7][8] , acting as its co-chaperone 8 , and to Rho kinase I and II (ROCKI and ROCKII), inhibiting their activity 3,[9][10][11] .…”
mentioning
confidence: 99%
“…Morgana is a ubiquitous chaperone protein, essential for Drosophila and mouse development [1][2][3] . Morgana binds to the Heat Shock Protein 90 (HSP90) 1,2,[4][5][6][7][8] , acting as its co-chaperone 8 , and to Rho kinase I and II (ROCKI and ROCKII), inhibiting their activity 3,[9][10][11] . Our laboratory also demonstrated that Morgana is a component of the IKK complex, essential to sustain NF-κB activation 12,13 .…”
mentioning
confidence: 99%